Eco-Play: Mengajarkan Cinta Lingkungan melalui Permainan Tradisional untuk Anak Usia Dini di Raudhatul Athfal Kecamatan Sukaraja - Deswita, Deswita; Lailah, Febri Shollihatul; Aisyah, Nisa; Fitri, Najihatul; Hayati, Kurnia (Universitas Muhammadiyah Prof. DR. Hamka (UHAMKA Press), 2025)
Background: ECO-PLAY is a program designed to teach early childhood about the importance of love for the environment through traditional games, with the increasing issue of children who are more familiar with online games than traditional games, this program is expected to form children's awareness and concern for the environment from an early age, so that they grow into a generation that is more responsible for the sustainability of the ecosystem. Method: This community service program is implemented using methods applied to teachers, including interactive workshops, practical training, making learning modules, case studies and sharing best practices, and evaluation and feedback. Results: This community service activity produces children who understand the importance of the environment, cooperation and solidarity in groups, and also the use of natural materials for learning. Conclusion: This community service activity not only provides education to children about the importance of the environment, but also provides real experience for teachers in innovating learning techniques that are fun for children.